Diffusion radiomics analysis of intratumoral heterogeneity in a murine prostate cancer model following radiotherapy: Pixelwise correlation with histology. Issue 2 (8th February 2017) - Lin, Yu‐Chun; Lin, Gigin; Hong, Ji‐Hong; Lin, Yi‐Ping; Chen, Fang‐Hsin; Ng, Shu‐Hang; Wang, Chun‐Chieh
Abstract : Purpose: To investigate the biological meaning of apparent diffusion coefficient (ADC) values in tumors following radiotherapy. Materials and Methods: Five mice bearing TRAMP‐C1 tumor were half‐irradiated with a dose of 15 Gy. Diffusion‐weighted images, using multiple b‐values from 0 to 3000 s/mm 2, were acquired at 7T on day 6. ADC values calculated by a two‐point estimate and monoexponential fitting of signal decay were compared between the irradiated and nonirradiated regions of the tumor. Pixelwise ADC maps were correlated with histological metrics including nuclear counts, nuclear sizes, nuclear spaces, cytoplasmic spaces, and extracellular spaces. Results: As compared with the nonirradiated region, the irradiated region exhibited significant increases in ADC, extracellular space, and nuclear size, and a significant decrease in nuclear counts ( P < 0.001 for all). Optimal ADC to differentiate the irradiated from nonirradiated regions was achieved at a b‐value of 800 s/mm 2 by the two‐point method and monoexponential curve fitting. ADC positively correlated with extracellular spaces ( r  = 0.74) and nuclear sizes ( r  = 0.72), and negatively correlated with nuclear counts ( r  = –0.82, P < 0.001 for all). Conclusion: As a radiomic biomarker, ADC maps correlating with histological metrics pixelwise could be a means of evaluating tumor heterogeneity and responses to radiotherapy. Level of Evidence: 1 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2017;46:483–489